THORAX CT-SCAN EXAMINATION RESULT OF COVID-19 PATIENTS - Omat Rachmat; Ilma Fiddiyanti; Lukmana Lokarjana; Erika Mustika Rahayu (Fakultas Kedokteran Gigi Unjani, 2022)
Coronavirus disease 2019 (COVID-19) is a pandemic disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2 Anyone could have asymptomatic to severe symptoms. COVID-19 manifests in the lungs, so Radiological examinations, such as X-rays and CT-Scans are needed. The CT-Scan thorax is an examination to assess the progression, severity, and comorbidities based on the consensus of the Radiology Society of North America (RSNA). The purpose of this literature review is to discuss and provide information about the SARS-CoV-2 virus, pathogenesis and pathophysiology, clinical symptoms, and the results of the COVID-19 thorax CT scan. This research is a literature study, which is a type of research that collects, manages, uses, and reviews research data sourced from scientific research journals, previous research manuscripts, and textbooks. The results of the literature review are discussions used to strengthen the management of COVID-19 based on symptoms with a CT-Scan of the thorax. DOI : 10.54052/jhds.v2n1.p15-26